When price determines choice: A study on immunity supplement consumers in urban pharmacy - I Gusti Ngurah Dwi Wiryawan; Ardi Saputra (Privietlab, 2025)
The increased use of immune supplements, particularly in urban areas post-pandemic, has raised questions about the reasons behind consumer purchasing behavior regarding these products. This study aims to explore the impact of product quality, price, and brand image on consumer purchasing decisions for immune supplements in Indonesia, specifically for purchases through national pharmacy chains. The study used a quantitative approach, surveying 125 urban consumers using purposive sampling, and analyzed the data using multiple linear regression analysis. The results showed that price was the most significant decision driver, followed by brand image and product quality, with all factors significantly influencing purchasing decisions. This study provides insights into how price, trust, and perceived value significantly influence consumer purchasing decisions. The results are practical for pharmacy managers and health product companies in developing pricing, branding, and product communication strategies aimed at health-conscious urban residents who prefer affordable products.